2003
DOI: 10.1074/jbc.m213052200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for a Glucose Analog of Blood Group H Antigen as a Mediator of Leukocyte-Endothelial Adhesion via Intracellular Adhesion Molecule 1

Abstract: The 4A11 antigen is a unique cytokine-inducible antigen up-regulated on rheumatoid arthritis synovial endothelium compared with normal endothelium. In soluble form, this antigen, Lewis y -6/H-5-2 (Le y /H), or its glucose analog, 2-fucosyllactose (H-2g), mediates angiogenesis. The Le y /H antigen is structurally related to the soluble E-selectin ligand, sialyl Lewis x , and is selectively expressed in skin, lymphoid organs, thymus, and synovium, suggesting that it may be important in leukocyte homing or adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…Furthermore, H type 2 antigens mediate leukocyte-endothelial adhesion through intracellular adhesion molecule, suggesting that they are involved in the progression of inflammation (Zhu et al 2003). On the other hand, A type 3 determinants seemed to be carried on vWF in endothelial cells in inflamed tissues (Figure 5), suggesting that aberrantly expressed A type 3 antigens play a role in blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H type 2 antigens mediate leukocyte-endothelial adhesion through intracellular adhesion molecule, suggesting that they are involved in the progression of inflammation (Zhu et al 2003). On the other hand, A type 3 determinants seemed to be carried on vWF in endothelial cells in inflamed tissues (Figure 5), suggesting that aberrantly expressed A type 3 antigens play a role in blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysis and immunoblotting were performed as described previously (37,38). Briefly, freshly isolated human MNCs were incubated in 6-well plates for at least 12 hours (2 ϫ 10 6 /well) in serum-free RPMI 1640 prior to stimulation with 10 nM CXCL16 for various time periods.…”
Section: Methodsmentioning
confidence: 99%
“…26,36,37 It is a downstream target of Src, PI3K, p38, and Jak2 and a key transcription factor regulating inflammation. 28,38,39 In this study, we demonstrate a direct effect of rhMIF in up-regulating VCAM-1 and ICAM-1 in human peripheral blood (PB) monocytes (MNs) using cell-surface enzyme-linked immunosorbent assays (ELISAs). We report the role of Src, PI3K, p38, and NFB in up-regulating these adhesion molecules.…”
mentioning
confidence: 99%
“…on May 11, 2018. by guest www.bloodjournal.org From Cell adhesion molecules may be up-regulated via different protein tyrosine kinases such as Src, phosphatidylinositol 3 kinase (PI3K), Erk1/2, Jak2, Stat3, and NFB. [26][27][28][29] We and others have shown that vascular endothelial growth factor and sE-selectin mediate angiogenesis via Src kinases. 30,31 Src family kinases mediate the multistep process of leukocyte adhesion, migration, and accumulation at inflammatory sites by the interaction of a number of adhesion molecules on leukocytes and endothelial cells.…”
mentioning
confidence: 99%